Impact of user behavior on network performance reliability - Juan ZHAO; Ping GUO; Hong-zhong DENG; Jun WU; Yue-jin TAN; Min ZHANG (Tongxin xuebao)
Based on a lattice network,a user access behavior model was established to describe the statistical characteristics of user behavior including the clustering characteristics and the power law distribution.The phase transition point was used to analysis the influence of the statistical characteristics of user behavior on the network performance reliability.It was shown that the network performance reliability almost independent on the degree distribution of the server-visited bipartite network;however the hot changing of the small subset with the high degree server nodes improved the network reliability.The strength,frequency and the duration of the clustering characteristics have certain impact on the phase transition of network performance reliability.The phase transition point of network performance reliability moved to the right with the increase of the difference between the number of active users when the clustering characteristics happened and don’t.